Repetitive Arm Movements During Sleep: A Polysomnographic Assessment - Mohammad Torabi-Nami; Samrad Mehrabi; Sabri Derman (Basic and Clinical Neuroscience, 2016)
Sleep-related movement disorders should be differentiated from parasomnias, sleep-associated behavioral disorders, and epilepsy. Polysomnography (PSG) is the gold standard in evaluating such disorders. Periodic leg movement disorder during sleep (PLMS), hypnic jerks, bruxism, rhythmic movement disorder, restless legs syndrome, and nocturnal leg cramps have broadly been discussed in the literature. However, periodic arm movement disorder in sleep (PAMS) is a less-appreciated entity perhaps because arm surface electromyography is not an integral part of the standard polysomnography. Results from our PSG study in a case suspected for PAMS prompted us to herewith discuss this problem.